2018
DOI: 10.15517/ma.v29i2.29511
|View full text |Cite
|
Sign up to set email alerts
|

Respuesta foliar y radical del maíz a la fertilización biológica-química en un suelo Luvisol

Abstract: An alternative to replace the excessive use of chemical fertilizers is the use of soil microorganisms. In this regard, using nitrogen fixingbacteria (N) and mycorrhizal fungi may improve the growth of different crops. The objective was to evaluate the influence of Rhizophagus intraradices and Azospirillum brasilense, as well as the addition of chemical fertilizers on foliar and root response of maize crop in Luvisol soil. The study was conducted from October 2014 to January 2015 at the Technological Institute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
2
5
0
6
Order By: Relevance
“…For stem diameter the best treatment was Ab + 50% IF as revealed by the statistical signif icance (Fisher's LSD, P ≤ 0.05) test when compared with the rest of the treatments (Table 1), which agrees with Zarazúa et al (2009) who reported that maize plant inoculation with A. brasilense conferred plant development, and above all, increased in stem length and weight. However, Xiu (2014 2 ) and Montejo-Martínez et al (2015; reported satisfactory increments in stem diameter la rentabilidad agroproductivo-f inanciera del maíz grano. Además, es muy factible la f ito-estimulación con Pseudomonas amigables con el entorno natural y útiles en procesos biológicos modernos que fomenten la sucesión de etapas por las que atraviesa el cultivo (Couillerot et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For stem diameter the best treatment was Ab + 50% IF as revealed by the statistical signif icance (Fisher's LSD, P ≤ 0.05) test when compared with the rest of the treatments (Table 1), which agrees with Zarazúa et al (2009) who reported that maize plant inoculation with A. brasilense conferred plant development, and above all, increased in stem length and weight. However, Xiu (2014 2 ) and Montejo-Martínez et al (2015; reported satisfactory increments in stem diameter la rentabilidad agroproductivo-f inanciera del maíz grano. Además, es muy factible la f ito-estimulación con Pseudomonas amigables con el entorno natural y útiles en procesos biológicos modernos que fomenten la sucesión de etapas por las que atraviesa el cultivo (Couillerot et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Ello concuerda con lo expuesto por Zarazúa et al (2009) quienes ref ieren que la inoculación de plantas de maíz con A. brasilense les conf iere desarrollo vegetativo y, sobre todo, aumento en la longitud y peso del tallo. Sin embargo, Xiu (2014 2 ) y Montejo-Martínez et al (2015; reportan incrementos satisfactorios en el diámetro del tallo cuando se les inocula con HMA, A. brasilense y reduce la dosis del fertilizante a la mitad.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Durante el mes de junio de 2016, en parcelas que variaron entre 0.5 a 1 ha, de acuerdo con la disponibilidad de terreno cultivado con maíz de cada productor, se tomaron cinco muestras de suelo de 0 a 0.30 m, por ser la profundidad donde se encuentra el mayor volumen de raíces (Montejo-Martínez et al, 2018). Con las cinco muestras se conformó una muestra homogénea por sitio y se enviaron al laboratorio Fertilizab ® donde se realizaron los análisis de acuerdo con la Norma Of icial Mexicana (SEMARNAT, 2002) para medir pH, capacidad de intercambio catiónico total (CIC), porcentaje de saturación de cationes intercambiables, contenido de materia orgánica (MO) y acidez intercambiable (Al 3+ y H + ).…”
Section: Diseño De Muestreo Y Análisis Químicosunclassified